“Girls Just Wanna Have Fun(damental) Human Rights:” How the Women’s Convention and Belgium combat Gender Stereotypes - Bo Minou Beintema (Udayana Journal of Law and Culture, 2020)
To put it simply, the purpose of the Women’s Convention is to end discrimination on the basis of sex. The inclusion of Article 5, paragraph (a), which focuses on fixed gender roles that get in the way of that goal, provides one of the ways in which they aim to do so. State parties cannot hide behind their respective traditions or customs as to why the realisation of International Human Rights ultimately depends on gender. A question that arises is what does this mean for States in terms of concrete obligations. This article aims to provide an answer to that question by exploring Article 5 (a) and the notion of extra-legal measures, in particular. Equally, it will take a closer look at how one of the State parties, namely Belgium, is doing in this regard both in theory as in practice. By conducting literary research it becomes apparent that State parties have to adopt national laws and/or instruments. Furthermore, they have to incorporate extra-legal measures as well. Meaning, they should incorporate measures to influence the mindsets of people regarding gender equality through means such as education, the media and public information projects, for instance. Although Belgium continues to struggle with effective implementation of its laws and policies due to its inherent complex institutional structure. It can still be said that its well on its way to combat gender inequality in light of Article 5 (a). Ultimately, Article 5 (a) brings meaning to every right in the Women’s Convention. Considering, that it is only when gender equality is reached both before the law and in practice that women will be able to enjoy Human Rights.